Effect of maternity waiting homes use on maternal and perinatal birth outcomes and its challenges in Amhara region, Northwest Ethiopia - Molla, Muluye; Tesfa, Mulugeta; Alle, Atsede; Molla, Firehiwot; Aschale, Abiot; Endalew, Bekalu; Gietaneh, Wodaje (Frontiers in Global Women's Health, 2023)
Background Women's death due to complications of pregnancy and childbirth is still high. Maternity waiting homes are one of the strategies to reduce it. However, there is limited evidence on the effect of using maternity waiting homes on birth outcomes, particularly in this study area. Therefore, this study was aimed to estimate the effect of staying in maternity waiting homes use on maternal and perinatal birth outcomes and its challenges in the Amhara region, Northwest Ethiopia 2018. Methods Institutional-based comparative cross-sectional study using both quantitative and qualitative approaches was conducted. Data were collected using structured questionnaire interviews, in-depth interview and chart reviews. Propensity score matching analysis was used to estimate the effect of maternity waiting homes use on birth outcomes. Propensity score matching analysis was used to match potential differences in background characteristics that affect pregnancy outcomes between comparison groups. We used thematic analysis for qualitative data. Result A total of 548 pregnant mothers (274 stayed in maternity waiting homes 274 did not stay) took part in this study. The proportion of adverse birth outcomes of mothers who stayed in maternity waiting homes were 15(5.5%) which is lower than those who didn't stay 35 (12.8%). After matching with baseline covariates, mean difference of adverse maternal birth outcomes, the difference between didn't use maternity waiting home and used was 10.4%, at (t = 3.78) at 5% level of significance. Similarly, the mean adverse perinatal birth outcomes difference between mothers who didn't use MWHs and used was 11% (t = 4.33). Conclusions Maternity waiting home showed a significant positive effect on birth outcomes. Mothers who stayed in the maternity waiting homes had low adverse maternal and perinatal birth outcomes compared to non-users. Accommodations and quality health care services were the challenges mothers faced during their stay in the maternity waiting homes. Therefore, all concerned bodies should give attention accordingly to maternity waiting home services to reduce adverse birth outcomes through the strengthening of the quality of health care provided.